Copper foil, preparation method thereof, negative electrode containing copper foil and lithium ion battery

A copper foil with ultrafine grains and nano twins, produced via pulse electroplating, addresses the breakage issue of traditional copper foils, enhancing battery safety and stability through improved mechanical properties.

CN119256122APending Publication Date: 2025-01-03JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202480002654.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional copper foils used as negative electrode current collectors in lithium-ion batteries are prone to breakage due to excessive stretching during the charging and discharging process, leading to safety issues and reduced service life.

Method used

A copper foil with ultrafine grains and nano twins, produced through pulse electroplating technology, featuring an average grain size of 0.2-0.4 μm, an area-weighted average grain size of 0.3-0.8 μm, and a nano twin grain proportion greater than 50%, with a tensile strength of 600-900 MPa and elongation greater than 5%, is developed.

Benefits of technology

The copper foil exhibits high tensile strength and elongation, effectively resisting volume changes in silicon-carbon negative electrodes, improving battery cycle stability and safety by preventing rupture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256122A_ABST
    Figure CN119256122A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a copper foil, a preparation method thereof, a negative electrode containing the copper foil and a lithium ion battery. The copper foil comprises ultra-fine grains and nano twin crystals, the average grain size is 0.2-0.4 mu m, the area weighted average grain size is 0.3-0.8 mu m, and the proportion of the nano twin crystals in the copper foil is larger than 50%. The copper foil is prepared through a pulse electroplating technology, and the technology can control the average grain size and the proportion of nano twin crystals in the copper foil, so that the copper foil has high tensile strength and high ductility. According to the preparation method of the copper foil, a specific electrolyte is adopted at the same time, the tensile strength of the copper foil can reach 600-900 MPa, and the ductility is larger than 5%. When the copper foil is applied to the lithium ion battery, the volume expansion rate of a negative electrode material after charge-discharge circulation can be reduced, copper foil breakage caused by repeated volume change of the negative electrode material in the charge-discharge process is prevented, the cycle life of the battery is prolonged, and the safety of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a copper foil and a preparation method thereof, and a negative electrode and a lithium ion battery comprising the same. Background Art

[0002] As the number of electric vehicles and the installed capacity of renewable energy continue to increase, the demand for lithium-ion batteries is increasing rapidly.

[0003] Electrolytic copper foil is widely used as negative electrode current collector of lithium-ion batteries due to its excellent conductivity. At the same time, due to its good mechanical properties, it is also the main bearer of stress generated during battery manufacturing and use.

[0004] The main trend in the development of lithium-ion batteries today is to improve energy density and safety. The theoretical specific capacity of traditional graphite negative electrodes is only 372Ah / kg, while the new silicon-carbon negative electrode is expected to achieve an energy density of more than 3000Wh / kg. The iteration of negative electrode materials will be the main way to improve battery energy density in the future. However, the volume of silicon-carbon negative electrode materials will shrink / expand significantly with the deintercalation / intercalation of lithium ions. This phenomenon leads to volume changes during the battery's charging and discharging process, resulting in repeated stretching of the copper foil as a stress carrier. Traditional copper foil current collectors are prone to breakage due to excessive stretching during this process, resulting in a short circuit inside the battery, affecting the safety and service life of the battery. Summary of the invention

[0005] The invention provides a copper foil and a preparation method thereof, and a negative electrode and a lithium ion battery comprising the same, so as to solve the problem that the existing copper foil used as a current collector is easily broken due to excessive stretching during the battery charging and discharging process.

[0006] According to a first aspect of the present invention, the present invention provides a copper foil comprising ultrafine grains and nano twins, wherein the average grain size of the copper foil is 0.2-0.4 μm, the area-weighted average grain size is 0.3-0.8 μm, and the proportion of nano twin grains in the copper foil measured by EBSD is greater than 50%.

[0007] Furthermore, the elongation of the copper foil is greater than 5%.

[0008] Furthermore, the tensile strength of the copper foil is 600-900 MPa.

[0009] Furthermore, the copper foil has a thickness of 4-10 μm.

[0010] According to a second aspect of the present invention, the present invention further provides a method for preparing a copper foil, the preparation method comprising the following steps:

[0011] The original foil is obtained by electrolyzing the electrolyte with a pulse power supply at a predetermined pulse width and duty cycle; the current density of the pulse power supply is 8000-15000A / m 2 , the pulse width is 1 to 50 ms, and the duty cycle is 1% to 30%; the electrolyte includes an electrolytic additive, and the electrolytic additive includes a brightener with a content of 12-20 mg / L, an auxiliary brightener with a content of 4-10 mg / L, a leveler with a content of 2-8 mg / L, polyethylene glycol with a content of 2-10 mg / L, and an inhibitor with a content of 6-30 mg / L;

[0012] The original foil is washed and passivated to obtain electrolytic copper foil.

[0013] Further, the electrolyte also contains 60-120 g / L of copper ions, 90-150 g / L of sulfuric acid and 20-40 mg / L of chloride ions. Further, the brightener includes an organic sulfide; preferably, the brightener includes one or more of sodium polydisulfide propane sulfonate, sodium polydisulfide propane sulfonate and sodium 3-mercapto-1-propane sulfonate.

[0014] Further, the auxiliary brightener includes a nitrogen-containing organic sulfide; preferably, the auxiliary brightener includes one or more of polyisothiourea propane sulfonic acid inner salt, 3-benzothiazolyl-2-thiol propane sulfonate sodium, N,N-dimethyl-sodium propane sulfonate and tetrahydrothiazolidinethione.

[0015] Further, the leveler includes a nitrogen-containing small molecule compound; preferably, the leveler includes one or more of 2-mercaptopyridine, amino-4-methylbenzothiazole and tricyclazole.

[0016] Furthermore, the molecular weight of polyethylene glycol is 4000-10000.

[0017] Further, the inhibitor includes a polyether compound having a molecular weight of less than or equal to 2000; preferably, the inhibitor includes one or more of polyethylene glycol with a molecular weight of 400-1000, polypropylene glycol with a molecular weight of 800-2000, and a copolymer of ethylene glycol and propylene glycol with a molecular weight of 400-1000.

[0018] Furthermore, the mass ratio of polyethylene glycol to the polyether compound is 1:2-1:4.

[0019] Furthermore, the temperature of the electrolytic treatment is 50-60°C; during the electrolytic treatment, the upper flow rate of the electrolyte is 40-50m 3 / h.

[0020] According to a third aspect of the present invention, the present invention further provides a negative electrode, comprising a negative electrode current collector, wherein the negative electrode current collector comprises a metal foil, and the metal foil comprises the copper foil provided in any embodiment of the first aspect.

[0021] According to a fourth aspect of the present invention, the present invention further provides a lithium-ion battery, comprising a negative electrode, wherein the negative electrode comprises the negative electrode provided by any embodiment of the third aspect above.

[0022] The technical solution provided by the present invention has the following beneficial effects:

[0023] The copper foil provided by the present invention has a highly refined grain size, and the mechanical properties of the electrolytic copper foil can be regulated by introducing a nano twin structure in the microscopic grain structure. The coherent grain boundary of the nano twin can not only effectively hinder the movement of dislocations and play a role in strengthening the material, but also when the deformation stress is high enough, the dislocation can also slip on the coherent twin interface, thereby effectively improving the plasticity and work hardening ability of the material, and ensuring that the electrolytic copper foil has a high elongation.

[0024] The invention discloses a method for preparing a copper foil using pulse electroplating technology. Compared with the conventional direct current electroplating technology, the invention realizes controllable adjustment of the crystal microstructure. Electrolytic copper foils with different microscopic grain sizes are constructed using pulse electroplating technology. By adjusting power supply parameters, including peak current, pulse width and duty cycle, the growth cycle and stress release process of microscopic copper grains can be changed, thereby adjusting the grain size and nano twin ratio, so that the tensile strength of the electrolytic copper foil can be adjusted within the range of 600-900 MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 EBSD crystal structure diagram of the cross section of the electrolytic copper foil prepared according to Example 4 of the present invention;

[0027] Figure 2 EBSD crystal structure diagram of the cross section of the electrolytic copper foil prepared according to Comparative Example 1 of the present invention;

[0028] Figure 3 It is a comparison chart of the tensile strength and elongation of the electrolytic copper foil prepared according to Example 4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] As analyzed in the background art, the electrolytic copper foil in the prior art is easily broken due to excessive stretching during the battery charging and discharging process, which in turn causes a short circuit inside the battery, affecting the safety and service life of the battery.

[0031] Generally, grain refinement of polycrystalline metal materials can effectively improve their tensile strength, but the plasticity of the material will be greatly reduced. Therefore, it is difficult to obtain copper foil with both ultra-high tensile strength and high elongation by the traditional method of introducing grain boundary impurities. Nano-twinned metals have unique mechanical properties and can maintain good elongation while having extremely high tensile strength. This is due to the interaction between the coherent grain boundaries and dislocation defects inside the nano-twins. On the one hand, the twin boundaries can effectively hinder the movement of dislocations. When the stress is high enough, the dislocations react with the twin interface and pass through the twin interface; on the other hand, the twin interface is also the slip plane of the cubic close-packed (Face-centered cubic, FCC) metal material. Not only can dislocations move on the twin interface, but the coherent grain boundary can also provide storage space for dislocations generated during deformation, thereby effectively improving the elongation of the copper foil.

[0032] However, it is not easy to prepare nanoscale twin lamellae and realize the controllable growth of nanotwin structures. The formation of nanotwins is driven by dynamics. Increasing the cathode overpotential is beneficial to increase the nucleation rate of electrodeposition, thereby obtaining samples with finer grain sizes. According to the description of the Butler-Volmer equation in electrochemical theory, when the mass transfer effect is not considered, the polarization current increases exponentially with the increase of overpotential. Therefore, increasing the current density is a traditional method to increase cathode polarization. Further adding the mass transfer process, the Cu on the electrode surface under high current density 2+The rapid consumption of the twinned layer will lead to a significantly lower concentration than that in the bulk phase, thus generating a large concentration polarization and overpotential. However, studies have shown that the thickness of the twinned layer does not show a strong correlation with the current density during DC electroplating. This may be related to the lower energy of the coherent grain boundary than that of the ordinary large-angle grain boundary. Twins often nucleate at grain boundaries or trifurcated grain boundaries, and induce grain orientation changes through twinning, thereby reducing the overall grain boundary energy. During DC electroplating, a high cumulative stress will be generated due to the action of continuous current, so it often has a high grain boundary energy. In contrast, stress accumulation and relaxation during pulse electroplating are conducive to reducing grain boundary energy and promoting twin growth. When the pulse current is turned on, a large number of crystal nuclei are formed and tensile stress is generated in the coating, accumulating elastic strain energy; and during the interval of the pulse current, the tensile stress is released and causes the coating to produce nano twins by recrystallization. Therefore, adjusting the pulse width and duty cycle is the key to controlling the proportion of nano twins in the sample and obtaining extremely high tensile strength and high elongation. Pulse electroplating technology can also achieve a larger instantaneous current density, thereby obtaining a smaller grain size and higher tensile strength.

[0033] In a first typical embodiment of the present invention, the present invention provides a copper foil comprising ultrafine grains and nanotwins, wherein the average grain size is 0.2-0.4 μm, the area-weighted average grain size is 0.3-0.8 μm, and the proportion of nanotwin grains in the copper foil measured by EBSD is greater than 50%.

[0034] It should be noted that the grain size in conventional double-sided lithium battery copper foil is usually larger than 1 μm, and grains with a size less than 1 μm are defined as ultrafine grains. The ultrafine grains in this application refer to grains with a grain size less than 1 μm. The average grain size and area-weighted average grain size are measured by backscatter diffraction (EBSD). The two are calculated using the following formula:

[0035]

[0036] Where d is the size of a single grain, n d is the number of grains with size d, S d is the area of ​​the grain with size d. In the above scheme, the copper foil with the above average grain size and area-weighted average grain size has a highly refined grain size, so that the electrolytic copper foil can be guaranteed to have high tensile strength and high elongation. When the average grain size is too large, the tensile strength cannot reach the expected level due to the reduction of the grain boundary density contained therein. However, too small an average grain size will also introduce excessive grain boundary impurities, reduce the proportion of twin boundaries, and lead to a decrease in elongation.

[0037] In the above scheme, the electrolytic copper foil of the present invention has a high twinning ratio, and the mechanical properties of the electrolytic copper foil can be regulated by introducing a large number of nano-twin structures in the microscopic grain structure. The coherent grain boundaries of the nano-twins can not only effectively hinder the movement of dislocations and play a role in strengthening the material, but also when the deformation stress is high enough, the dislocations can also slip on the coherent twin interface, thereby effectively improving the plasticity and work hardening ability of the material. A higher twinning ratio (greater than 50%) helps to improve the elongation of the copper foil, while when the twinning ratio is low (less than or equal to 50%), it will lead to a decrease in elongation.

[0038] In some embodiments of the present invention, the elongation of the copper foil is greater than 5%.

[0039] In some embodiments of the present invention, the tensile strength of the copper foil is 600-900 MPa.

[0040] In the above scheme, the electrolytic copper foil of the present invention has high tensile strength and / or high elongation. The high tensile strength can effectively reduce the volume expansion rate of the silicon-carbon negative electrode material. At the same time, the higher elongation can reduce the risk of copper foil rupture during battery use, resulting in a reduction in battery cycle life, thereby improving the battery's cycle stability and safety.

[0041] In some specific embodiments of the present invention, the thickness of the electrolytic copper foil is 4-10 μm.

[0042] In the above scheme, by limiting the thickness of the electrolytic copper foil within the above range, it is beneficial to improve the battery processing quality and improve the battery performance. A copper foil thickness of less than 4 μm will increase the probability of abnormalities in the coating process of producing the battery and reduce the elongation. When the copper foil thickness is greater than 10 μm, the active material content in the battery is reduced due to the high thickness, and the capacity density of the battery is affected.

[0043] In a second typical embodiment of the present invention, the present invention further provides a method for preparing a copper foil, the method comprising the following steps:

[0044] The original foil is obtained by electrolyzing the electrolyte with a pulse power supply at a predetermined pulse width and duty cycle; the current density of the pulse power supply is 8000-15000A / m 2 , the pulse width is 1 to 50 ms, and the duty cycle is 1% to 30%; the electrolyte includes an electrolytic additive, and the electrolytic additive includes a brightener with a content of 12-20 mg / L, an auxiliary brightener with a content of 4-10 mg / L, a leveler with a content of 2-8 mg / L, polyethylene glycol with a content of 2-10 mg / L, and an inhibitor with a content of 6-30 mg / L;

[0045] The original foil is washed and passivated to obtain electrolytic copper foil.

[0046] It should be noted that the pulse width of the pulse power supply is defined as the time the power is turned on in each cycle, and the duty cycle refers to the ratio of the power on time (ton) in each cycle to the total time period (ton+toff), that is, ton / (ton+toff)×100%.

[0047] In the above scheme, pulse electroplating technology is used to electrolyze and prepare copper foil. The pulse power supply effectively makes up for the problem that the grain size is reduced when the tensile strength of copper foil is improved by electrolytic additives in the past, and a large number of large-angle grain boundaries are introduced, resulting in a significant decrease in the elongation of copper foil. Based on the electrolytic additives of a specific composition, the present invention further defines the current density, pulse width and duty cycle of the pulse power supply during the pulse electroplating process. A higher peak current density can increase the overpotential of the electrodeposition reaction and increase the driving force for the deposition of copper ions on the surface of the cathode roller, thereby obtaining smaller crystalline particles. On the other hand, too fast a deposition rate will also lead to uneven crystal growth rate, so it is necessary to control the pulse width to control the size of the crystal growth.

[0048] The above preparation method can not only obtain an electrolytic copper foil with extremely high tensile strength, but also ensure that the elongation is greater than 5%, thereby better resisting the volume change caused by material expansion during battery use and improving the cycle stability and safety of the battery.

[0049] Preferably, in some embodiments, the peak current density of the pulse power supply used includes but is not limited to 8000A / m 2 , 9000A / m 2 、10000A / m 2 、11000A / m 2 、12000A / m 2 、13000A / m 2 、14000A / m 2 、15000A / m 2 , which is much higher than the current density used in conventional electrolysis conditions (6000-7000A / m 2 ).

[0050] Higher current density combined with smaller pulse width can significantly reduce the generation of large-sized crystals. Preferably, in some embodiments, the pulse width used includes but is not limited to 1ms, 3ms, 5ms, 7ms, 10ms, 20ms, 30ms, 40ms, 50ms. A single pulse can only generate crystal particles of a few nanometers in size, and a large number of nano-twin stacked structures are formed during multiple repeated pulses.

[0051] A suitable duty cycle can reduce the concentration polarization on the electrode surface. Copper ions and additives are consumed and deposited on the electrode surface during the power-on period, and are replenished during the power-off period. Preferably, in some embodiments, the duty cycle used includes but is not limited to 1%, 5%, 10%, 13%, 15%, 20%, 25%, 30%. A higher pulse peak current density or a longer pulse width consumes more active substances, so the above duty cycle can ensure that copper ions and additives are better enriched on the surface.

[0052] The present application can use conventional electrolytes in combination with the above-mentioned pulse electrolysis conditions to achieve the above effects. Alternatively, the electrolyte can be prepared by a common preparation method, such as dissolving the metal element copper in sulfuric acid, adding electrolyte additives and hydrochloric acid thereto, stirring evenly to obtain a first solution, and filtering and purifying the first solution to obtain an electrolyte.

[0053] In some embodiments, the electrolyte further comprises 60-120 g / L copper ions, 90-150 g / L sulfuric acid, and 20-40 mg / L chloride ions.

[0054] In the above scheme, by limiting the amount of each component in the electrolyte within a reasonable range, the components can play a better synergistic role, which is more conducive to the preparation of electrolytic copper foil with high tensile strength and high elongation.

[0055] In some embodiments of the present invention, the brightener includes an organic sulfide; preferably, the brightener includes one or more of sodium polydisulfide propane sulfonate (SPS), sodium polydisulfide propane sulfonate (SES) and sodium 3-mercapto-1-propane sulfonate (MPS).

[0056] In some embodiments of the present invention, the auxiliary brightener includes a nitrogen-containing organic sulfide; preferably, the auxiliary brightener includes one or more of polyisothiourea propane sulfonate (UPS), 3-benzothiazolyl-2-thiol propane sulfonate sodium (ZPS), N,N-dimethyl-sodium propane sulfonate (DPS) and tetrahydrothiazolidinethione (TTT).

[0057] In the above scheme, the electrolytic additive uses an organic sulfide brightener in combination with a nitrogen-containing organic sulfide auxiliary brightener, which can obtain an electrolytic copper foil with extremely high tensile strength and effectively improve the elongation of the electrolytic copper foil. The reason is that during the copper crystal growth process, organic sulfides tend to be specifically adsorbed on the (111) crystal plane with high atomic density, and achieve grain refinement by inhibiting the growth of specific crystal planes. This specific adsorption often causes the crystals inside the copper foil to present a clear (111) texture, resulting in the grains easily sliding along specific crystal planes when the copper foil is stretched, so the tensile strength and elongation are low. However, due to the influence of heteroatoms, nitrogen-containing organic sulfides will change their own adsorption characteristics, aggregate to the (200) crystal plane with low atomic density, and reduce the (111) crystal plane texture ratio. In short, the texture phenomenon generated when generating nano twins can be effectively reduced by using an organic sulfide brightener and a nitrogen-containing organic sulfide auxiliary brightener.

[0058] Preferably, in some embodiments, the organic sulfide brightener used includes but is not limited to 12 mg / L, 13 mg / L, 14 mg / L, 15 mg / L, 16 mg / L, 17 mg / L, 18 mg / L, 19 mg / L, 20 mg / L in terms of concentration in the electrolyte, and the nitrogen-containing organic sulfide auxiliary brightener used includes but is not limited to 4 mg / L, 5 mg / L, 6 mg / L, 7 mg / L, 8 mg / L, 9 mg / L, 10 mg / L in terms of concentration in the electrolyte.

[0059] In some specific embodiments of the present invention, the leveler includes a nitrogen-containing small molecule compound; preferably, the leveler includes one or more of 2-mercaptopyridine (2-MP), 2-amino-4-methylbenzothiazole (AMBT) and tricyclazole (TCA).

[0060] In the above scheme, the electrolytic additive uses a nitrogen-containing small molecule compound to replace the traditional collagen leveler to better meet the requirements of higher diffusion speed of additive molecules under pulse electroplating conditions due to higher frequency and peak current. At the same time, the nitrogen-containing small molecule compound leveler has a stronger adsorption capacity on the copper foil surface due to its higher charge density, and can be introduced into the grain boundary as a doping substance, which plays a role in improving the tensile strength to a certain extent.

[0061] Preferably, in some embodiments, the nitrogen-containing small molecule compound leveler used includes but is not limited to 2 mg / L, 3 mg / L, 4 mg / L, 5 mg / L, 6 mg / L, 7 mg / L, and 8 mg / L in terms of concentration in the electrolyte.

[0062] In some specific embodiments of the present invention, the molecular weight of polyethylene glycol is 4000-10000 (hereinafter referred to as high molecular weight polyethylene glycol).

[0063] In some specific embodiments of the present invention, the inhibitor includes a polyether compound, and the molecular weight of the polyether compound is less than or equal to 2000. The polyether compound can be a homopolymer polyether compound or a copolymer polyether compound commonly used in electrolyte inhibitors. Preferably, the inhibitor includes one or more of polyethylene glycol with a molecular weight of 400-1000, polypropylene glycol with a molecular weight of 800-2000, and a copolymer of ethylene glycol and propylene glycol with a molecular weight of 400-1000.

[0064] In the above scheme, the electrolytic additive uses a relatively low molecular weight polyether or its copolymer as an auxiliary inhibitor. Compared with high molecular weight polyethylene glycol, low molecular weight polyether molecules have a higher diffusion rate, so they can replenish the inhibitor consumed on the cathode surface in time during the short off time of the high frequency pulse.

[0065] Experiments show that by combining high molecular weight polyethylene glycol and low molecular weight polyether in a specific mass ratio (such as 1:2-1:4, further exemplified as 1:2, 1:3 or 1:4) as electroplating inhibitors, the synergistic effect of the two can further effectively increase the proportion of nanotwins in the electrolytic copper foil, thereby achieving extremely high tensile strength while maintaining a high elongation.

[0066] Preferably, in some embodiments, the polyethylene glycol used includes but is not limited to 2 mg / L, 4 mg / L, 6 mg / L, 8 mg / L, 10 mg / L in concentration in the electrolyte, and the polyether inhibitor used includes but is not limited to 6 mg / L, 12 mg / L, 18 mg / L, 24 mg / L, 30 mg / L in concentration in the electrolyte.

[0067] The electrolyte temperature and upper flow rate used in the electrolytic treatment of the present invention refer to the conventional direct current electrolytic copper foil conditions. In some embodiments of the present invention, the temperature of the electrolytic treatment is 50-60°C; during the electrolytic treatment, the upper flow rate of the electrolyte is 40-50m 3 / h.

[0068] In a third typical embodiment of the present invention, the present invention further provides a negative electrode, including a negative electrode current collector, the negative electrode current collector includes a metal foil, and the metal foil includes the above-mentioned copper foil.

[0069] In some embodiments, the negative electrode further includes an active material layer disposed on at least one side of the negative electrode current collector, and the negative electrode active material layer may include carbon-based active materials such as graphite and hard carbon. In addition, the negative electrode active material also includes one or more of the group consisting of simple substances or oxides of elements such as Si, Ge, Sn, Zn, Ni, Co and Li. In addition, the negative electrode active material layer also includes a conductive agent and a binder.

[0070] In some specific embodiments of the present invention, the preparation method of the negative electrode is as follows:

[0071] Commercially available silicon-carbon negative electrode material, conductive carbon black, SBR (styrene-butadiene rubber) and CMC (carboxymethyl cellulose) are mixed in high-purity water to prepare a slurry; preferably, the amount of each raw material in the slurry is, by weight: 95 parts of commercially available silicon-carbon negative electrode material, 2 parts of conductive carbon black, 2 parts of SBR (styrene-butadiene rubber), and 1 part of CMC (carboxymethyl cellulose).

[0072] Next, the obtained slurry was coated on one side of the copper foil using a doctor blade, with a single-side loading of 7±0.5 mg / cm 2 , the electrode sheet coated with negative electrode material was dried by gradient heating at 115°C. Then the other side of the copper foil was coated. After drying, the dried copper foil sample was pressed using a roller press to make the electrode density 1.75±0.05g / cm 3 The coated copper foil was then die-cut into negative electrode sheets of 60 mm × 80 mm in size, and the thickness of the negative electrode sheets was measured with a micrometer.

[0073] In a fourth typical embodiment of the present invention, the present invention further provides a lithium-ion battery, which includes the above-mentioned negative electrode.

[0074] The beneficial effects of the present invention will be described below in conjunction with specific embodiments and comparative examples.

[0075] In the present invention, if the specific technology or conditions are not specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If the manufacturer of the instruments is not specified, they are all conventional products that can be purchased through regular channels. The raw materials used in the present invention can be easily purchased in the domestic market.

[0076] The test methods for the microstructure and basic physical properties of the electrolytic copper foil prepared in all embodiments of the present invention are as follows:

[0077] EBSD test: The microstructure of the copper foil samples of each embodiment and comparative example was observed using a C-Swift EBSD detector manufactured by Oxford Instruments, UK. In order to facilitate the observation of the grain boundary profile of the material, the cross section was polished for 20 minutes using an ion mill in advance.

[0078] Tensile strength and elongation test: According to the test method GB / T29847-2013, the tensile strength and elongation of the electrolytic copper foil were tested at a strain rate of 0.8 mm / s and room temperature (about 25°C) using the HY-0230 universal material testing machine manufactured by Shanghai Hengyi Precision Instrument Co., Ltd. The tensile test specimen is a strip specimen with a total length of 100 mm and a width of 15 mm. Repeat the measurement three times and take the average value as the final tensile strength and elongation of the sample.

[0079] The preparation and testing methods of lithium-ion batteries are as follows:

[0080] By weight, 95 parts of commercially available silicon-carbon negative electrode material, 2 parts of conductive carbon black, 2 parts of SBR (styrene-butadiene rubber), and 1 part of CMC (carboxymethyl cellulose) were mixed in high-purity water to prepare slurry.

[0081] Next, the obtained slurry was coated on one side of the copper foil using a doctor blade, with a single-side loading of 7±0.5 mg / cm 2 , the electrode sheet coated with negative electrode material was dried by gradient heating at 115°C. Then the other side of the copper foil was coated. After drying, the dried copper foil sample was pressed using a roller press to make the electrode density 1.75±0.05g / cm 3 The coated copper foil was then die-cut into negative electrode sheets of 60 mm × 80 mm in size, and the thickness of the negative electrode sheets was measured with a micrometer.

[0082] Next, the obtained negative electrode sheet was assembled with a commercially available separator, electrolyte and positive electrode sheet to manufacture a soft-pack battery. The battery was charged and discharged 100 times at a rate of 2C. The battery was then disassembled and the negative electrode sheet was taken out. The thickness of the sheet after the cycle was measured using a micrometer, and the expansion rate was calculated based on the difference in thickness before and after the cycle. At the same time, a strong flashlight was used to observe whether the sheet was damaged and transparent.

[0083] The present invention describes a double-glazed copper foil having a D (Drum) surface and an A (Air) surface, wherein the D surface is the surface that is attached to the cathode roller, and the other surface is the A surface.

[0084] Example 1

[0085] This embodiment provides an electrolytic copper foil, and the preparation method thereof comprises the following steps:

[0086] (1) dissolving copper metal in sulfuric acid to form a sulfuric acid-copper sulfate solution, then adding an electrolytic additive and hydrochloric acid and stirring evenly to obtain a first solution; adding 1 g / m 3 The activated carbon and diatomaceous earth are stirred, and then the organic impurities and suspended matter are removed with a stainless steel filter cloth. After two filtrations, the pure electrolyte for electrolysis is obtained.

[0087] Among them, the copper ion concentration in the obtained electrolyte is 86g / L, the sulfuric acid concentration is 120g / L, the chloride ion (hydrochloric acid) concentration is 20mg / L, and the organic sulfide brightener SPS13mg / L, nitrogen-containing organic sulfide auxiliary brightener UPS6mg / L, small molecule leveling agent 2-MP 4mg / L, polyethylene glycol with a molecular weight of 4000 6mg / L, and polyether inhibitor (polyethylene glycol with a molecular weight of 400) 18mg / L are added to the electrolyte.

[0088] (2) The titanium roller is used as the cathode and the iridium-tantalum coated titanium plate is used as the anode. The above electrolyte is electrolyzed by a pulse power supply. The peak current density is 13000A / m 2 , pulse width 3ms, duty cycle 5%, to prepare copper foil with a thickness of 6μm. The electrolytic treatment temperature is 55℃, and the upper flow rate of the electrolyte is 45m 3 / h.

[0089] (3) Washing, passivating and drying the obtained copper foil to obtain an uncut finished electrolytic copper foil. Figure 1 The obtained electrolytic copper foil has ultra-fine grain size and uniform distribution.

[0090] Next, EBSD was used to observe and study the microstructure of the cross section of the electrolytic copper foil obtained by the pulse electroplating, and the average grain size, area-weighted average grain size and twin grain ratio of the sample were measured.

[0091] Next, the mechanical properties of the electrolytic copper foil obtained above were tested, and the tensile strength and elongation of the sample were obtained.

[0092] Then, the electrolytic copper foil is assembled into a soft-pack battery for cycle testing to check whether the negative electrode copper foil is damaged.

[0093] Example 2

[0094] This embodiment provides an electrolytic copper foil, and the preparation method thereof comprises the following steps:

[0095] (1) dissolving copper metal in sulfuric acid to form a sulfuric acid-copper sulfate solution, then adding an electrolytic additive and hydrochloric acid and stirring evenly to obtain a first solution; adding 1 g / m 3 The activated carbon and diatomaceous earth are stirred, and then the organic impurities and suspended matter are removed with a stainless steel filter cloth. After two filtrations, the pure electrolyte for electrolysis is obtained.

[0096] Among them, the copper ion concentration in the obtained electrolyte is 109g / L, the sulfuric acid concentration is 130g / L, the chloride ion (hydrochloric acid) concentration is 22mg / L, 16mg / L of SES and SPS in a mass ratio of 1:1, 4mg / L of auxiliary brightener TTT, 3mg / L of small molecule leveling agent AMBT, 4mg / L of polyethylene glycol with a molecular weight of 8000, and 12mg / L of polyethylene glycol with a molecular weight of 1000 are added to the electrolyte.

[0097] (2) The titanium roller is used as the cathode and the iridium-tantalum coated titanium plate is used as the anode. The above electrolyte is electrolyzed by a pulse power supply. The peak current density is 9000A / m 2 , pulse width 30ms, duty cycle 25%, prepare copper foil with thickness of 6μm. The temperature of electrolysis treatment is 55℃, and the flow rate of electrolyte is 45m 3 / h.

[0098] (3) washing, passivating and drying the obtained copper foil to obtain an uncut finished electrolytic copper foil.

[0099] Next, EBSD was used to observe and study the microstructure of the cross section of the electrolytic copper foil obtained by the pulse electroplating, and the average grain size, area-weighted average grain size and twin grain ratio of the sample were measured.

[0100] Next, the mechanical properties of the electrolytic copper foil obtained above were tested, and the tensile strength and elongation of the sample were obtained.

[0101] Then, the electrolytic copper foil is assembled into a soft-pack battery for cycle testing to check whether the negative electrode copper foil is damaged.

[0102] Example 3

[0103] This embodiment provides an electrolytic copper foil, and the preparation method thereof comprises the following steps:

[0104] (1) dissolving copper metal in sulfuric acid to form a sulfuric acid-copper sulfate solution, then adding an electrolytic additive and hydrochloric acid and stirring evenly to obtain a first solution; adding 1 g / m 3 The activated carbon and diatomaceous earth are stirred, and then the organic impurities and suspended matter are removed with a stainless steel filter cloth. After two filtrations, the pure electrolyte for electrolysis is obtained.

[0105] Among them, the copper ion concentration in the obtained electrolyte is 63g / L, the sulfuric acid concentration is 105g / L, the chloride ion (hydrochloric acid) concentration is 38mg / L, 15mg / L of SPS and MPS in a mass ratio of 1:1, 8mg / L of DPS, 2mg / L of small molecule leveling agent TCA, 3mg / L of polyethylene glycol with a molecular weight of 80000, and 9mg / L of propylene glycol with a molecular weight of 800 are added to the electrolyte.

[0106] (3) The titanium roller is used as the cathode and the iridium-tantalum coated titanium plate is used as the anode. The above electrolyte is electrolyzed by a pulse power supply. The peak current density is 11000A / m 2 , pulse width 10ms, duty cycle 20%, prepare copper foil with a thickness of 6μm. The electrolytic treatment temperature is 55℃, and the upper flow rate of the electrolyte is 45m 3 / h.

[0107] (3) washing, passivating and drying the obtained copper foil to obtain an uncut finished electrolytic copper foil.

[0108] Next, EBSD was used to observe and study the microstructure of the cross section of the electrolytic copper foil obtained by the pulse electroplating, and the average grain size, area-weighted average grain size and twin grain ratio of the sample were measured.

[0109] Next, the mechanical properties of the electrolytic copper foil obtained above were tested, and the tensile strength and elongation of the sample were obtained.

[0110] Then, the electrolytic copper foil is assembled into a soft-pack battery for cycle testing to check whether the negative electrode copper foil is damaged.

[0111] Example 4

[0112] This embodiment provides an electrolytic copper foil, and the preparation method thereof comprises the following steps:

[0113] (1) dissolving copper metal in sulfuric acid to form a sulfuric acid-copper sulfate solution, then adding an electrolytic additive and hydrochloric acid and stirring evenly to obtain a first solution; adding 1 g / m 3 The activated carbon and diatomaceous earth are stirred, and then the organic impurities and suspended matter are removed with a stainless steel filter cloth. After two filtrations, the pure electrolyte for electrolysis is obtained.

[0114] Among them, the copper ion concentration in the obtained electrolyte is 117g / L, the sulfuric acid concentration is 110g / L, the chloride ion (hydrochloric acid) concentration is 30mg / L, 19mg / L of SPS and MPS with a mass ratio of 1:1, 7mg / L of DPS and TTT with a mass ratio of 1:1, 6mg / L of small molecule leveler 2-MP, 7mg / L of polyethylene glycol with a molecular weight of 10000, and 21mg / L of ethylene glycol and propylene glycol copolymer with a molecular weight of 1000 are added to the electrolyte.

[0115] (2) The titanium roller is used as the cathode and the iridium-tantalum coated titanium plate is used as the anode. The above electrolyte is electrolyzed by a pulse power supply. The peak current density is 14000A / m 2 , pulse width 7ms, duty cycle 13%, to prepare copper foil with a thickness of 6μm. The electrolytic treatment temperature is 55℃, and the upper flow rate of the electrolyte is 45m 3 / h.

[0116] (3) washing, passivating and drying the obtained copper foil to obtain an uncut finished electrolytic copper foil.

[0117] Next, EBSD was used to observe and study the microstructure of the cross section of the electrolytic copper foil obtained by the pulse electroplating, and the average grain size, area-weighted average grain size and twin grain ratio of the sample were measured.

[0118] Next, the mechanical properties of the electrolytic copper foil obtained above were tested, and the tensile strength and elongation of the sample were obtained.

[0119] Then, the electrolytic copper foil is assembled into a soft-pack battery for cycle testing to check whether the negative electrode copper foil is damaged.

[0120] Example 5

[0121] This embodiment provides an electrolytic copper foil, and the preparation method thereof is different from that of the embodiment 4 only in that the duty cycle of the pulse power supply is 1%, and the rest is the same as that of the embodiment 4.

[0122] Example 6

[0123] This embodiment provides an electrolytic copper foil, and the preparation method thereof is different from that of the embodiment 4 only in that the duty cycle of the pulse power supply is 30%, and the rest is the same as that of the embodiment 4.

[0124] Example 7

[0125] This embodiment provides an electrolytic copper foil, and the preparation method thereof is different from that of the embodiment 4 only in that the pulse width of the pulse power supply is 5 ms, and the rest is the same as that of the embodiment 4.

[0126] Example 8

[0127] This embodiment provides an electrolytic copper foil, and the preparation method thereof is different from that of the embodiment 4 only in that the pulse width of the pulse power supply is 50 ms, and the rest is the same as that of the embodiment 4.

[0128] Example 9

[0129] This embodiment provides an electrolytic copper foil, the preparation method of which is different from that of embodiment 4 only in that the peak current density of the pulse power supply is 8000A / m 2 , the rest is the same as Example 4.

[0130] Example 10

[0131] This embodiment provides an electrolytic copper foil, the preparation method of which is different from that of embodiment 4 only in that the peak current density of the pulse power supply is 15000A / m 2 , the rest is the same as Example 4.

[0132] Embodiment 11

[0133] This embodiment provides an electrolytic copper foil, the preparation method of which is different from that of embodiment 4 only in that the concentration of the organic sulfide brightener in the electrolyte is 20 mg / L, the concentration of the nitrogen-containing organic sulfide auxiliary brightener is 6 mg / L, and the rest is the same as that of embodiment 4.

[0134] Example 12

[0135] This embodiment provides an electrolytic copper foil, and the preparation method thereof is different from that of Embodiment 4 only in that the concentration of the organic sulfide brightener in the electrolyte is 18 mg / L, and the concentration of the nitrogen-containing organic sulfide auxiliary brightener is 10 mg / L, and the rest is the same as that of Embodiment 4.

[0136] Embodiment 13

[0137] This embodiment provides an electrolytic copper foil, and the preparation method thereof is different from that of the embodiment 4 only in that the concentration of the small molecule leveler in the electrolyte is 5 mg / L, and the rest is the same as that of the embodiment 4.

[0138] Embodiment 14

[0139] This embodiment provides an electrolytic copper foil, and the preparation method thereof is different from that of Embodiment 4 only in that the concentration of polyethylene glycol in the electrolyte is 2 mg / L, and the concentration of the polyether inhibitor is 6 mg / L, and the rest is the same as that of Embodiment 4.

[0140] Embodiment 15

[0141] This embodiment provides an electrolytic copper foil, and the preparation method thereof is different from that of Embodiment 4 only in that the concentration of polyethylene glycol in the electrolyte is 10 mg / L, and the concentration of the polyether inhibitor is 30 mg / L, and the rest is the same as that of Embodiment 4.

[0142] Comparative Example 1

[0143] Comparative Example 1 is a comparative example of Example 4, which provides a high tensile strength copper foil prepared by a conventional direct current electroplating method, and its specific preparation steps are as follows:

[0144] (1) dissolving copper metal in sulfuric acid to form a sulfuric acid-copper sulfate solution, then adding an electrolytic additive and hydrochloric acid and stirring evenly to obtain a first solution; adding 1 g / m 3The activated carbon and diatomaceous earth are stirred, and then the organic impurities and suspended solids are removed with a stainless steel filter cloth, and then filtered twice to obtain a pure electrolyte for electrolysis. The copper ion concentration in the obtained electrolyte is 117g / L, the sulfuric acid concentration is 110g / L, and the chloride ion (hydrochloric acid) concentration is 30mg / L. SPS and MPS with a mass ratio of 1:1 are added to the obtained electrolyte, with a total of 19mg / L, DPS and TTT with a mass ratio of 1:1 are added to a total of 7mg / L, a small molecule leveler 2-MP 6mg / L, a polyethylene glycol with a molecular weight of 10000 7mg / L, and a copolymer of ethylene glycol and propylene glycol with a molecular weight of 1000 21mg / L.

[0145] (2) With the titanium roller as the cathode and the iridium-tantalum coated titanium plate as the anode, the above electrolyte was electrolyzed with a constant current power supply at a current density of 6500A / m 2 , to prepare a copper foil with a thickness of 6 μm. The temperature of the electrolytic treatment was 55°C, and the flow rate of the electrolyte was 45 m 3 / h.

[0146] (3) Washing, passivating and drying the obtained copper foil to obtain an uncut finished electrolytic copper foil. Figure 2 As shown, the obtained electrolytic copper foil has a larger average grain size, and the grain size distribution shows an obvious increasing trend from the D side to the A side.

[0147] Next, EBSD was used to observe and study the microstructure of the cross section of the electrolytic copper foil obtained by the pulse electroplating, and the average grain size, area-weighted average grain size and twin grain ratio of the sample were measured.

[0148] Next, the mechanical properties of the electrolytic copper foil obtained above were tested, and the tensile strength and elongation of the sample were obtained.

[0149] Then, the electrolytic copper foil is assembled into a soft-pack battery for cycle testing to check whether the negative electrode copper foil is damaged.

[0150] Comparative Example 2

[0151] This comparative example provides an electrolytic copper foil, the preparation method of which is different from that of Example 4 only in that the pulse width of the pulse power supply is 60 ms, and the rest is the same as that of Example 4.

[0152] Comparative Example 3

[0153] This comparative example provides an electrolytic copper foil, the preparation method of which is different from that of Example 4 only in that the duty cycle of the pulse power supply is 40%, and the rest is the same as that of Example 4.

[0154] Comparative Example 4

[0155] This comparative example provides an electrolytic copper foil, the preparation method of which is different from that of Example 4 only in that the peak current of the pulse power supply is 7000A / m 2 , the rest is the same as Example 4.

[0156] Comparative Example 5

[0157] This comparative example provides an electrolytic copper foil, the preparation method of which is different from that of Example 4 only in that the organic sulfide brightener in the electrolyte is 24 mg / L, the nitrogen-containing organic sulfide auxiliary brightener is 2 mg / L, and the rest is the same as Example 4.

[0158] Comparative Example 6

[0159] This comparative example provides an electrolytic copper foil, the preparation method of which is different from that of Example 4 only in that the concentration of the small molecule leveler in the electrolyte is 10 mg / L, and the rest is the same as that of Example 4.

[0160] Comparative Example 7

[0161] This comparative example provides an electrolytic copper foil, the preparation method of which is different from that of Example 4 only in that the concentration of polyethylene glycol in the electrolyte is 12 mg / L, the concentration of the polyether inhibitor is 36 mg / L, and the rest is the same as that of Example 4.

[0162] Table 1 below lists the microscopic grain size, basic physical properties and battery expansion rate test results of the electrolytic copper foil samples manufactured according to various embodiments and comparative examples of the present invention.

[0163] Table 1

[0164]

[0165]

[0166] First, Example 4 and Comparative Example 1 are samples prepared by pulse plating and DC plating in the same electrolyte, respectively. Figure 1 and Figure 2 The electrolytic copper foil prepared by direct current electroplating has a larger average grain size, and the grain size distribution shows a significant increasing trend from the D side to the A side, indicating that the pulse electroplating method used in Example 4 can effectively achieve grain refinement, and the discontinuous deposition of copper ions under the action of the pulse electric field also helps to obtain a consistent grain size distribution from the D side to the A side. On the other hand, the higher twin grain ratio of Comparative Example 1 is due to the uneven distribution of its grain size, and some larger twins contribute more grain boundary length and twin area. Figure 3The tensile extension curves of the electrolytic copper foil of Example 4 and Comparative Example 1 are compared. It can be seen that although the elongation of Comparative Example 1 is greater than that of Example 4, its tensile strength is lower, which is consistent with the average grain size and twin grain ratio shown in EBSD. The lower tensile strength causes a larger volume change during the charge and discharge process, and repeated stretching produces metal fatigue and leads to rupture.

[0167] In addition, Example 4 and Comparative Example 6 have similar tensile strength. However, due to the unreasonable electrolyte ratio, excessive doping grain boundaries are introduced, which reduces the proportion of nano twins, resulting in low elongation and easy rupture during the battery charging cycle. After the current collector is ruptured, the expansion restriction effect on the negative electrode material is weakened, so Comparative Example 6 also has a higher volume expansion rate.

[0168] In addition, Examples 1-15 achieve a tensile strength covering the range of 600-900 MPa while maintaining an elongation greater than 5% by adjusting power supply parameters (duty cycle, pulse width and peak current density) and / or electrolyte ratio.

[0169] In summary, the pulse electroplating technology of the present invention can be used to prepare an electrolytic copper foil with highly refined grain size, high nano twin ratio and ultra-high tensile strength, and such an electrolytic copper foil can effectively suppress the volume change of the silicon-carbon negative electrode material during the charge and discharge process. At the same time, the electrolytic copper foil of the present invention has a high elongation, which can effectively prevent the copper foil from breaking due to repeated volume changes of the silicon-carbon negative electrode material during the charge and discharge process, and the lithium ion battery negative electrode containing the electrolytic copper foil of the present invention has better cycle life and safety.

[0170] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A copper foil, characterized in that: The copper foil comprises ultrafine grains and nano twins, the average grain size of the copper foil is 0.2-0.4 μm, the area-weighted average grain size is 0.3-0.8 μm, and the proportion of nano twin grains measured by EBSD in the copper foil is greater than 50%.

2. The copper foil according to claim 1, characterized in that The elongation of the copper foil is greater than 5%.

3. The copper foil according to claim 1 or 2, characterized in that The tensile strength of the copper foil is 600-900 MPa.

4. The copper foil according to claim 1, characterized in that The copper foil has a thickness of 4-10 μm.

5. A method for preparing copper foil, characterized in that: The preparation method comprises the following steps: The original foil is obtained by electrolyzing the electrolyte with a pulse power supply at a predetermined pulse width and duty cycle; the current density of the pulse power supply is 8000-15000A / m 2 , the pulse width is 1 to 50 ms, the duty cycle is 1% to 30%; the electrolyte includes an electrolytic additive, and the electrolytic additive includes a brightener with a content of 12-20 mg / L, an auxiliary brightener with a content of 4-10 mg / L, a leveler with a content of 2-8 mg / L, polyethylene glycol with a content of 2-10 mg / L, and an inhibitor with a content of 6-30 mg / L; The raw foil is washed and passivated to obtain an electrolytic copper foil.

6. The preparation method according to claim 5, characterized in that: The electrolyte further comprises 60-120 g / L of copper ions, 90-150 g / L of sulfuric acid and 20-40 mg / L of chloride ions.

7. The preparation method according to claim 6, characterized in that: The brightener includes an organic sulfide; preferably, the brightener includes one or more of sodium polydisulfide propane sulfonate, sodium polydisulfide ethane sulfonate and sodium 3-mercapto-1-propane sulfonate; And / or, the auxiliary brightener includes a nitrogen-containing organic sulfide; preferably, the auxiliary brightener includes one or more of polyisothiourea propane sulfonate, sodium 3-benzothiazolyl-2-thiol propane sulfonate, sodium N,N-dimethyl-propane sulfonate and tetrahydrothiazolidinethione; And / or, the leveler includes a nitrogen-containing small molecule compound; preferably, the leveler includes one or more of 2-mercaptopyridine, amino-4-methylbenzothiazole and tricyclazole; And / or, the molecular weight of the polyethylene glycol is 4000-10000; And / or, the inhibitor comprises a polyether compound, the molecular weight of the polyether compound is less than or equal to 2000; preferably, the inhibitor comprises one or more of polyethylene glycol with a molecular weight of 400-1000, polypropylene glycol with a molecular weight of 800-2000, and a copolymer of ethylene glycol and propylene glycol with a molecular weight of 400-1000; And / or the mass ratio of the polyethylene glycol to the polyether compound is 1:2-1:

4.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The temperature of the electrolysis treatment is 50-60°C; during the electrolysis treatment, the flow rate of the electrolyte is 40-50m 3 / h.

9. A negative electrode, comprising a negative electrode current collector, wherein the negative electrode current collector comprises a metal foil, characterized in that: The metal foil comprises the copper foil according to any one of claims 1 to 4.

10. A lithium ion battery comprising a negative electrode, characterized in that: The negative electrode includes the negative electrode according to claim 9.

Citation Information

Cited By

  • Copper foil and preparation method thereof, lithium battery copper foil, current collector, pole piece, battery and electric device

    CN120077495A

  • Copper foil and its preparation methods, lithium battery copper foil, current collectors, electrodes, batteries and electrical devices

    CN120077495B

  • Secondary battery and preparation method therefor, and electric device

    WO2026041165A1

  • Copper foil, manufacturing method therefor, lithium-ion battery copper foil, current collector, electrode sheet, battery and electrical device

    WO2026148562A1

  • Current collector and preparation method, battery cell, battery device, and electric device

    WO2026171262A1